Guaranteed decentralized pursuit-evasion in the plane with multiple pursuers - Haomiao Huang; Wei Zhang; Ding, J.; Stipanovic, D. M.; Tomlin, C. J. (2011 50th IEEE Conference on Decision and Control and European Control Conference, 2011)
Pursuit-evasion games are an important problem in robotics and control, but games with many players are difficult to analyze and solve. This paper studies a game of multiple pursuers cooperating to capture a single evader in a bounded, convex, polytope in the plane. We present a decentralized control scheme based on the Voronoi partion of the game domain, where the pursuers jointly minimize the area of the evader's Voronoi cell. We prove that capturing the evader is guaranteed under this scheme regardless of the evader's actions, and show simulation results demonstrating the pursuit strategy.